Spontaneous Preterm Birth Is Associated with Differential Expression of Vaginal Metabolites by Lactobacilli-Dominated Microflora - Stafford, Graham P.; Parker, Jennifer L.; Amabebe, Emmanuel; Kistler, James; Reynolds, Steven; Stern, Victoria; Paley, Martyn; Anumba, Dilly O. C. (Frontiers in Physiology, 2017)
A major challenge in preventing preterm birth (PTB) is identifying women at greatest risk. This pilot study prospectively examined the differences in vaginal microbiota and metabolite profiles of women who delivered prematurely compared to their term counterparts in a cohort of asymptomatic (studied at 20-22, n = 80; and 26-28 weeks, n = 41) and symptomatic women (studied at 24-36 weeks, n = 37). Using 16S rRNA sequencing, the vaginal microbiota from cervicovaginal fluid samples was characterised into five Community State Types (CST) dominated by Lactobacillus spp.: CSTI (L. crispatus), CSTII (L. gasseri), CSTIII (L. iners), CSTV (L. jensenii); and mixed anaerobes - CSTIV. This was then related to the vaginal metabolite profile and pH determined by 1H-Nuclear Magnetic Resonance spectroscopy and pH indicator paper respectively. At 20-22w, the term-delivered women (TDW) indicated a proportion of CSTI-dominated microbiota > 2-fold higher compared to the preterm-delivered women (PTDW) (40.3 vs. 16.7%, P=0.0002), and a slightly higher proportion at 26-28w (20.7 vs. 16.7%, P=0.03). CSTV was > 2-fold higher in the PTDW compared to TDW at 20-22 (22.2 vs. 9.7%, P=0.0002) and 26-28w (25.0 vs. 10.3%, P=0.03). Furthermore, at 26-28w no PTDW had a CSTII-dominated microbiome, in contrast to 28% of TDW (P<0.0001). CSTI-dominated samples showed higher lactate levels than CSTV at 20-22w (P<0.01), and 26-28w (P<0.05), while CSTII-dominated samples indicated raised succinate levels over CSTV at 26-28w (P<0.05). These were supported by Principal coordinates analysis, which revealed strong clustering of metabolites according to CST. In addition, the CSTI-dominated samples had an average pH of 3.8, which was lower than those of CSTII – 4.4, and CSTV – 4.2 (P<0.05). Elevated vaginal lactate and succinate were associated with predominance of CSTI and II over CSTV in women who delivered at term compared with their preterm counterparts. This suggests that L. jensenii-dominance and decreased lactate and/or succinate could increase the risk of PTB, while L. crispatus/gasseri may confer some protection against inflammation-associated PTB and highlight the need for further study in this area.